Benthic insects of the El Tala River (Catamarca, Argentina): longitudinal variation of their structure and the use of insects to assess water quality - Colla,MF (2013)
The aim of this work was to determine the structure of the benthic entomofauna and its variation along the El Tala River (Catamarca, Argentina). Five sampling stations were established, considering the location of nearby housing with respect to the watercourse. The following variables were determined in situ: altitude, latitude and longitude, bedstream width, river depth, river-current speed, water and air temperatures. Benthic insects were collected with a square parcel sampler of 0.09-m2 area and 300-µm net opening and identified to the family level. Faunal density, richness, and diversity exhibited a longitudinal variation. From sampling Stations 1 (reference site) to 3, the number of orders and families decreased, whereas in sampling Station 4 those values increased and continued to do so through to Station 5 (downstream station). Station 5 showed the highest family richness (17) and the highest value for the Shannon-Wiener index (2.74) and the lowest value in Simpson's Dominance index (D = 0.22). These values could be explained because of the self-cleansing capabilities of the river downstream. The water quality of El Tala River is Class I (very clean and non-impacted), according to the results obtained from the application of the biotic Biological-Monitoring–Working-Party and Average-Store-per-Taxon indices.